2014
DOI: 10.1186/1471-2458-14-940
|View full text |Cite
|
Sign up to set email alerts
|

Promoting healthy eating and physical activity among school children: findings from Health-E-PALS, the first pilot intervention from Lebanon

Abstract: BackgroundIn Lebanon, childhood obesity doubled during the past decade. Preventive measures should start early in life and Schools are considered an important environment to promote energy balance health behaviours. School-based programmes promoting healthy lifestyles are lacking. The purpose of this study was to evaluate the feasibility and effectiveness of a multicomponent school-based intervention to promote healthy eating and physical activity (and prevent obesity) with school children aged 9–11 years in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(173 citation statements)
references
References 39 publications
2
129
0
13
Order By: Relevance
“…41 Healthy eating: the first step to living longer and better The risk regarding the acquisition of chronic diseases such as obesity, diabetes and hypertension, especially in childhood, decreases considerably with a diversified and balanced diet rich in almonds, fruits, legumes, and vegetables, with an adequate intake of water, and avoiding the consumption of highly processed foods, carbonated beverages, and artificial juices. [48][49][50][51] However, the high cost of healthier foods has made the access more difficult by economically disadvantaged populations. 52 Meanwhile, the supply and demand for low-cost foods with lower nutritional value has increased, particularly in educational institutions for children and young people.…”
Section: Interventions In Healthcare Environmentsmentioning
confidence: 99%
“…41 Healthy eating: the first step to living longer and better The risk regarding the acquisition of chronic diseases such as obesity, diabetes and hypertension, especially in childhood, decreases considerably with a diversified and balanced diet rich in almonds, fruits, legumes, and vegetables, with an adequate intake of water, and avoiding the consumption of highly processed foods, carbonated beverages, and artificial juices. [48][49][50][51] However, the high cost of healthier foods has made the access more difficult by economically disadvantaged populations. 52 Meanwhile, the supply and demand for low-cost foods with lower nutritional value has increased, particularly in educational institutions for children and young people.…”
Section: Interventions In Healthcare Environmentsmentioning
confidence: 99%
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
“…The parental version had a somewhat higher Cronbach's alpha value, which can be explained by the fact that the current DKQ was based on a knowledge questionnaire that was originally developed for adults [17]. The internal validity of the current questionnaire is higher compared to previously developed knowledge questionnaires for younger Lebanese children (aged 9-11 years; alpha: 0.66) [25], and for older adolescents (aged 17-18 years; alpha ranged from 0.5 to 0.75) [41].…”
Section: Internal Reliabilitymentioning
confidence: 88%
“…However, prior to planning any health promotion program targeting this particular age category, it is necessary to have reliable tools to assess the current levels of dietary knowledge and adherence to determine the effectiveness of such interventions later on. To our knowledge, studies assessing the relationship between dietary knowledge and adherence are scarce [25], particularly in the Middle East. Correspondingly, there is a paucity of reliable Arabic questionnaires measuring dietary knowledge and adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation